2023
DOI: 10.1039/d2nj05871e
|View full text |Cite
|
Sign up to set email alerts
|

Siloxane-decorated MXene nanosheet-reinforced EP composites with outstanding flame retardancy and liquid-oxygen compatibility for ultra-low-temperature applications

Abstract: Endowing epoxy resins (EPs) with satisfactory liquid-oxygen compatibility and ultra-low-temperature mechanical properties is an intractable challenge in the current aerospace industry. Appropriate flame retardants can provide systems with the above...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…MXenes, a new member of two-dimensional (2D) material family, has shown promise in reducing friction and wear due to their layered structure of transition metal carbides. 10–13 So far, MXenes have caught considerable attention in the fields of energy storage, 14–18 polymer, 19 environments, 20,21 and thermal management. 22,23 Previous studies showed that adding limited amount of MXene to base oils such as polyalphaolefin (PAO) and silicon oil can reduce the coefficient of friction.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, a new member of two-dimensional (2D) material family, has shown promise in reducing friction and wear due to their layered structure of transition metal carbides. 10–13 So far, MXenes have caught considerable attention in the fields of energy storage, 14–18 polymer, 19 environments, 20,21 and thermal management. 22,23 Previous studies showed that adding limited amount of MXene to base oils such as polyalphaolefin (PAO) and silicon oil can reduce the coefficient of friction.…”
Section: Introductionmentioning
confidence: 99%